Advantages of time-dependent diffusion MRI for quantitative microstructural mapping in breast tumors - Bao, Lei; Li, Sijie; Wang, Zhuo; Sun, Yang; Qiu, Ying; Shen, Zhiwei; Zhang, Xiaoxiao; Chen, Xue; Zhang, Xiaoxiao; Zhang, Junyu; Ji, Tiefeng (Frontiers in Oncology, 2025)
ObjectivesTime-dependent diffusion MRI (TD-MRI) can measure tumor tissue microstructure, but its effectiveness in differentiating benign from malignant breast tumors is unclear. This study aims to investigate the diagnostic value of TD-MRI microstructural features for distinguishing between benign and malignant breast tumors.MethodsThis prospective study included 44 patients with malignant breast tumors and 28 with benign tumors. All subjects underwent the IMPULSED protocol on a 3.0-T MRI scanner. Imaging data were analyzed using least squares fitting in MATLAB, yielding Dex (extracellular diffusivity), Vin (intracellular volume fraction), Dmean (cell diameter), Vin/Dmean, and ADC values. The molecular subtypes of breast cancer are classified based on immunohistochemistry (IHC) results.ResultsMalignant tumors exhibited significantly lower Dmean (17.37 ± 2.74 µm vs. 22.47 ± 3.85µm, p<0.0001), higher Vin (0.41 ± 0.13% vs. 0.19 ± 0.10%, p<0.0001), and higher Vin/Dmean (2.13 ± 0.66 vs. 0.93 ± 0.61, p<0.0001) compared to benign tumors. No significant difference was found in Dex (2.15 ± 0.28 um2/ms vs. 2.25 ± 0.31 um2/ms, p>0.05). Strong correlations were observed: positive between ADC and Dmean, and negative between ADC and both Vin and Vin/Dmean. AUC values for Vin (0.92; 95% CI: 0.86-0.99), and Vin/Dmean (0.91; 95% CI: 0.83-0.98) surpassed those for ADC.ConclusionTD-MRI microstructure mapping effectively differentiates benign from malignant breast tumors, highlighting its potential to improve diagnostic accuracy for lesions.